Experiment Study: The Effect of Tournament Incentive Schemes on Budgetary Slack and Moral Reasoning as Moderation - Rabbani, Inayah Abdillah; Nahartyo, Ertambang; Mattunruang, Andi Aris; Maksar, Muhammad Sofian (The Indonesian Journal of Accounting Research, 2025)
A number of empirical findings on tournament incentive schemes proved the effectiveness and efficiency of tournament incentive schemes in improving the performance of employees and managers. However, the latest study connecting the tournament incentive schemes to negative behavior proved that the tournament incentive schemes encourage opportunistic behavior in companies. This study aims to investigate the effect of implementing tournament incentive schemes in two different schemes and the effect of different levels of individual moral reasoning on budgetary slack and to conduct investigations on the role of moral reasoning in moderating the tournament incentive scheme to budgetary slack. This study was designed using a 2x2 experimental method between subjects. The results of this study indicate greater budgetary slack for the condition of a repeated tournament incentive scheme rather than the conditions of a grand tournament incentive scheme. It is less common in groups for individuals with high moral reasoning rather than low moral reasoning groups. Theoretically, this research contributes to expanding the explanation of tournament theory for negative efforts involving the role of cognitive moral development (CMD) theory. In addition, this study can be basic in choosing alternative incentive schemes that can be used to create a conducive environment and be independent of unethical behavior, especially for the process of budgeting in the companies.